Averaging principle for slow–fast stochastic Burgers equation driven by α-stable process. (May 2020) - Chen, Yalan; Shi, Yinghui; Sun, Xiaobin
Abstract: In this paper, we study the averaging principle for a slow–fast stochastic system driven by α -stable process with α ∈ ( 1, 2 ), where the slow and fast components are the stochastic Burger equation and the stochastic reaction–diffusion equation respectively. The proof is based on the Khasminskii's time discretization and the techniques of stopping times.